2019
DOI: 10.1108/jrf-07-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between price and volume in the Bitcoin market

Abstract: Purpose Bitcoin has recently become the focal point of investors as a digital currency and an alternative payment method. Despite Bitcoin being in the spotlight, a gap in the literature on its price-setting behaviors has been observed. This study aims to contribute to the literature by investigating the relationship between Bitcoin price and volume in the period between January 1, 2012 and April 7, 2018 through a symmetric and asymmetric causality test. Design/methodology/approach Daily price and volume data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(30 reference statements)
5
16
0
Order By: Relevance
“…Their results reveal that volume cannot help predicting volatility of Bitcoin price return. Gemici and Polat (2019) conduct a causality test between volume and Bitcoin price and found a causality relationship was determined from price to volume. Their findings are very interesting: a unilateral causality relationship was determined from negative shocks in Bitcoin prices to negative shocks in trading volume, the same is observed from positive shocks in trading volume to positive shocks in prices.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Their results reveal that volume cannot help predicting volatility of Bitcoin price return. Gemici and Polat (2019) conduct a causality test between volume and Bitcoin price and found a causality relationship was determined from price to volume. Their findings are very interesting: a unilateral causality relationship was determined from negative shocks in Bitcoin prices to negative shocks in trading volume, the same is observed from positive shocks in trading volume to positive shocks in prices.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Such price movements are unusual for traditional currencies, suggesting that the determinants for price formation do not follow rules established in previous theories (Ciaian et al, 2016), or in the words of Mai et al (2018) traditional explanatory variables for currency valuation fall short. Gemici and Polat (2019) find a unilateral causality relationship determined from negative shocks in bitcoin prices to negative shocks in trading volume as well as from positive shocks in trading volume to positive shocks in prices. Also, some studies found evidence that bitcoin prices are a financial bubble (Geuder et al, 2019;Chaim and Laurini, 2019).…”
Section: Introductionmentioning
confidence: 81%
“…In other words, Bitcoin is high-risk, and investors continue to trade and expand their trading volume precisely because Bitcoin assures them that the price will continue to rise. At the same time, the weak effect of Bitcoin trading volume on price also prevents investors from being dissatisfied with Bitcoin's price drop [7].…”
Section: Related Researchmentioning
confidence: 99%